Unmaking Goliath : community control in the face of global capital - DeFilippis, James (Routledge, 2004)
Arguing against those who say that our communities are powerless in the face of footloose corporations, DeFilippis considers what localities can do in the face of heightened capital mobility in order to retain autonomy and further social justice.